Multiregional representations of intertemporal decision making in human single neurons - Jay L. Gill; Mahmoud Omidbeigi; Jihye Ryu; Nanthia Suthana; Jonathan C. Kao; Ausaf Bari (Scientific Reports)
Abstract Understanding the neural mechanisms underlying delay discounting—the tendency to prefer smaller, immediate rewards over larger, delayed rewards—is critical for elucidating the etiology of impulsive decision-making, a hallmark of several psychiatric conditions including substance use and impulse control disorders. Here, we investigate single-neuron activity in the orbitofrontal cortex (OFC), hippocampus, and amygdala of nine human participants performing a delay discounting task. Intracranial recordings yielded a total of 193 single units (50 OFC, 68 amygdala, and 75 hippocampus) and reveal distinct neural correlates of decision-making, including representations of choice preferences and decision difficulty across all three regions. Analyses demonstrate preferential encoding of choice in the OFC. Additionally, we report that hippocampal activity reflects interindividual differences in discounting rates, with stronger representation observed in participants with slower temporal discounting. These findings provide novel insights into the multiregional neural computations underlying intertemporal decision-making and their relationship to impulsive behaviors.